The load balancing algorithm in cloud computing environment - Haozheng Ren; Yihua Lan; Chao Yin (2012 2nd International Conference on Computer Science and Network Technology, 2012)
With the users and the types of application on the cloud computing platform increasing, it becomes a critical problem about how to use the resources in the system effectively to ensure service level agreements (SLA). The load balancing algorithm is an important means to achieve efficient utilization of resources. This paper presents a dynamic load balancing algorithm based on virtual machine migration under cloud computing environment. The algorithm proposed the trigger strategy based on the fractal methods. The strategy determines the timing of the virtual machine migration through forecasting the timing to determine the timing of the virtual machine migration, which can avoid the problem of the peak instantaneous load trigger. Comparing with the other algorithms, such as ant colony and honey bees, this algorithm can achieve using of resources more balance. Finally, we test the system and the experimental results show that the algorithm can achieve load balancing and improve system performance.